Marketing Strategy to Increase Room Occupancy Rate at Aston Sunset Beach Resort Gili Trawangan - Andri Gunawan; Dhea Ananda Chantika Rahman; Putu Rio Satria Mahaditha; I Made Ngurah Satria Wibawa Oktaviadi; I Made Andika Pramudya Utama Winada; Ketut Surata; Putu Utama (PT FORMOSA CENDEKIA GLOBAL, 2025)
In this study, the marketing strategy in increasing room occupancy rates at Aston Sunset Beach Resort Gili Trawangan is reviewed. This study uses a descriptive qualitative approach to examine the marketing strategy in increasing room occupancy rates at Aston Sunset Beach Resort Gili Trawangan, the purpose of this study is to determine the right marketing strategy in increasing room occupancy rates at the Aston Sunset Beach Resort Gili Trawangan Hotel. The analysis tool used is SWOT Analysis consisting of IE Matrix, IFAS / EFAS, and SWOT Matrix. Based on the analysis, it is known that the position of Aston Sunset Beach Resort Gili Trawangan is currently in quadrant V, namely the stability strategy position with an IFAS score of 2.62 and an EFAS score of 2.53. In the SWOT / TOWS matrix, there are four alternative strategies that can be applied by Aston Sunset Beach Resort Gili Trawangan, namely Optimizing cooperation with travel agents, Increasing promotion through social media and other online platforms to reach a wider audience.